A new MEMS based variable capacitor with wide tunability, high linearity and low actuation voltage. Issue 2 (February 2015) - Afrang, Saeid; Mobki, Hamed; Sadeghi, Morteza H.; Rezazadeh, Ghader
Abstract We have proposed a new RF MEMS variable capacitor to achieve high linearity, wide tunability and low actuation voltage. The idea is based on increasing the linear region in the gap between the plates of the capacitor. It is done by adding a fixed-fixed beam below the fixed-free beam. The fixed-free beam is one plate of the capacitor. The voltage is applied to the fixed-free beam. In the vicinity of the pull-in voltage, the fixed-free beam losses its equivalent stiffness. The fixed-fixed beam is located in the vicinity of pull in situation of the fixed-free beam. This condition increases the equivalent stiffness of the fixed-free beam and allows the beam to continue moving down linearly and consequently increases the maximum capacitance of the structure. Geometrical and material property effects of the second beam on the linearity, tunability and voltage are investigated. The governing nonlinear equation for static deflection of the beam based on the Euler–Bernoulli beam theory has been presented.